Sensitivity of the reproductive system of male-rats to isolated and combined external exposure activity (1.0 Gy) and magnetic field of industrial frequency (50 Hz) - Vereschako, Genadiy G.; Chueshova, Natalya V.; Bakshayeva, Marharyta A.; Kazlou, Aliaksandr E.; Tsukanova, Elena V.; Shalatonin, Valeriy I. (Journal of the Belarusian State University. Ecology, 2018)
We studied the influence of the isolated and combined action of external irradiation at the dose of 1,0 Gy (source – 137Cs, dose rate 46 cGy/min) and magnetic field of the industrial frequency (50 Hz, 0.4 mT, 4 hours/day, 5 days/week, number of days of exposure – 28) on the condition of the reproductive system of male Wistar rats at different times after exposure. A decrease in the testes weight after external irradiation, disintegration of the spermatogenesis process, a decrease in the glutathione content and an increase in the activity of the GPO in the testis tissue, a significant deterioration of the quantitative and qualitative indices of epididymal spermatozoa, an increase in the necrotic and programmed sperm death after these effects. The combined effect of external irradiation (1,0 Gy) and MP IF (50 Hz) is accompanied by a modification of the action of each of them and in some cases led to effects exceeding the effect of each of them separately. Changes in the studied indicators indicate a high sensitivity of the reproductive system of males to the studied anthropogenic factors of the environment.
Keywords: male rats reproductive systems; external irradiation at a dose of 1,0 Gy; MP of IF (50 Hz); relative mass; spermatogenesis; epididymal spermatozoa; quantity cells; viability; apoptosis; necrosis; fructose; glyceraldehyde3-phosphate dehydrogenase (GAPDH); acrosyn; glutathione; glutathione peroxidase (GPO)